LEGAL PROTECTION REGARDING PHYSICAL VIOLENCE CRIMINAL ACTS AGAINST CHILD VICTIMS IN THE KAMPAR RESORT POLICE OFFICE - Benny Putra; Yeni Triana; Tri Anggara Putra (JILPR Journal Indonesia Law and Policy Review, 2026)
Against child victims at the Kampar District Police reveals a persistent gap between the ideal norms of child protection law and their implementation in law enforcement practice. This study aims to analyze the legal protection provided, the obstacles encountered, and the efforts undertaken in handling criminal acts of physical violence against child victims at the Kampar District Police. The research employs a sociological legal research method with an empirical approach, utilizing interviews, field observations, and literature review. The findings indicate that legal protection for child victims of physical violence at the Kampar District Police is fundamentally supported by a strong legal framework, particularly the Child Protection Act and relevant criminal law provisions. In practice, law enforcement officers have attempted to apply the principle of the best interests of the child through a humane examination approach, protection of the victim’s identity, and restrictions on interaction between the victim and the perpetrator. However, the implementation of such legal protection has not been fully optimal due to various cultural, structural, and normative obstacles. The challenges encountered include the low willingness of victims and their families to report incidents of violence due to fear, social pressure, and dependence on the perpetrator; difficulties in evidence gathering caused by limited evidence and the psychological condition of child victims; as well as inadequate supporting facilities and infrastructure and suboptimal intersectoral coordination in the protection and recovery of child victims. These conditions demonstrate a gap between adequate legal substance and legal structures and culture that have not fully supported the effective protection of children. Efforts to address these obstacles include strengthening legal socialization and public education to increase awareness and reporting courage, optimizing evidentiary processes through multidisciplinary approaches involving medical professionals and psychologists, and enhancing investigators’ capacity and inter-agency coordination in the field of child protection. Thus, legal protection for child victims of physical violence should not only focus on law enforcement against perpetrators but also on fulfilling justice, legal certainty, and recovery for child victims.